Lifeworlds of female bonded labourers among the Sahariya tribe. Issue 2 (17th February 2023) - Samonova, Elena
ABSTRACT: Debt bondage is one of the most widespread forms of unfree labour today. The majority of the existing studies focuses on bonded labourers as a homogenous group rather than examining group dynamics within the population of bonded labourers. This paper tries to overcome these limitations and examines experiences of women bonded labourers from the Sahariya tribe in India. It argues that gendered norms intersect with other patterns of structural violence creating a situation where women are doubly exploited but also opening new (limited) agentic spaces for these women.